2016
DOI: 10.1039/c5ra27132k
|View full text |Cite
|
Sign up to set email alerts
|

An efficient composite magnetocaloric material with a tunable temperature transition in K-deficient manganites

Abstract: This paper reports on a magnetic material with high steady relative cooling power (RCP) over a temperature range from 325 to 275 K induced by potassium-deficiency in polycrystalline samples of La0.8K0.2−x□xMnO3 (x = 0, 0.1 and 0.2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 30 publications
(32 reference statements)
1
9
1
Order By: Relevance
“…The obtained results reveal that both samples have crystallized in the rhombohedral structure belonging to the R3C space group. The structural and magnetic properties have been reported earlier by us [14].…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The obtained results reveal that both samples have crystallized in the rhombohedral structure belonging to the R3C space group. The structural and magnetic properties have been reported earlier by us [14].…”
Section: Resultssupporting
confidence: 64%
“…From magnetic measurements, a second-order magnetic phase transition from the paramagnetic to the ferromagnetic state was observed. The Curie Temperature T C decreased with increasing x, from 325 for x = 0 to 300 K for x = 0.1 [14]. Figure 2 shows the temperature (T) dependence of the zero field resistivity (T).…”
Section: Resultsmentioning
confidence: 97%
“…For a eld of 50 kOe, the Sr-0.18 compound exhibit a DS M value of 4.61 J kg À1 K À1 at 310 K, and for Sr-0.27 compound, the DS M reaches a maximum value of 4.11 J kg À1 K À1 at 276 K. In our previous work, we reported a DS M value of 4.78 J kg À1 K À1 at 364 K for the pristine compound and 5.08 J kg À1 K À1 at 352 K for Sr-0.09 compound for a eld change of 50 kOe. 37 However, in the present case, we have achieved a near room temperature (310 K) MCE with a signicant DS M value (4.61 J kg À1 K À1 ) for Sr-0.18 compound which is larger than that reported for numerous perovskite manganites 29,31,35,45,47 Apart from the spin, charge and orbital ordering, the conventional DE interaction is the only favourable mechanism behind the entropy change in the pristine compound. 37 However, from the magnetization and magnetocaloric properties, it can be understood that the presence of Mn 2+ ions in decient compounds enhances the ferromagnetism and DS M due to the multiple DE interaction via Mn 3+ -O 2À -Mn 2+ -O 2À -Mn 4+ path.…”
Section: Resultscontrasting
confidence: 62%
“…[28][29][30][31][32][33][34][35][36][37] Recently, many reports have demonstrated that the creation of deciency at the rare Earth and alkaline rare Earth sites alter the Mn 2+ /Mn 3+ /Mn 4+ ratio which severely affect the magnetic and magnetocaloric properties. [37][38][39][40][41][42][43][44][45][46][47][48][49] The structure of manganites is imperfect and contain vacancy type point defects, called Schottky defects due to the cyclic temperature changes during synthesis and sintering process. 50,51 The presence of cation (V (c) ) and anion (V (a) ) vacancies strongly inuence the properties of the manganites and causing a change in the stability of the perovskite structure.…”
Section: Introductionmentioning
confidence: 99%
“…However, Zhang et al [21] observed that Tc decreased with increase in the grain size in the range of 24.4-240 nm. It is known that this variation of Tc is controlled by the electron bandwidth W and the mobility of eg electrons [11,22,23]. In fact, the structure, magnetism, and the magnetocaloric effect are very correlated, primarily by the bandwidth W.…”
Section: Resultsmentioning
confidence: 99%